Electrostatics of Silicon Nano Transistor - Lalit Singh; B.P. Tyag (Журнал нано- та електронної фізики)
Nano Transistor represents a unique system for exploring physical phenomena pertaining to charge transport at the nano scale and is expected to play a critical role in future evolution of electronic and optoelectronic devices. This paper summarizes some of the essential electrostatics of nano Metal Oxide Semiconductor Field effect Transistor (MOSFET) and their electrical properties. Though the general focus of this work is on surface potential yet the first part presents a brief discussion of the independence of charge at the top of the barrier in the channel of MOS Transistor on Drain voltage. The quantum capacitance is discussed at length. The superposition theorem is used, thereafter, to obtain an expression for self consistent potential in the channel. Finally the I-V characteristics of the device are explored using Landauer formalism. The simulated results for a device are observed to represent the realistic behaviour of the device.